(3efjI GdfahS aj EXgGQ GdRjfI dcd YQhSs - (3Ydj Hf eMeO Hf CjOeQ GdpLrdnOcj, YR GdOjf,J (B742 (3g` s
(3ChdgG (B:s
(3aUd hCbhd GeG GdcHGQjJ agi hGMOI HGdfhY s
(3BNQgG (B:s
(3hdjcf gPG GdcdGe dcJGHfG (B" (3efjI GdfahS(B" (3gh GdceGd hGdNJGe hUdi Gddg Ydi eMeO hBdg GdWGgQjf GdeYShejf s
(3Vef eLehY , JQJjHgG (B: (3ef U (B234 - (3U(B240s
(3GdehLhO efg aUd ai CUfGa GdcHQjJ hUfGYJg hGSJYeGdg ai CYeGd GdcjejGAs
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B5 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B28s
Keywords: (3GdcjejGA h GdWHjYjGJs